Pengaruh teknologi AI terhadap transformasi pendidikan di era revolusi industri 4.0 - Fitriana, Nuzul (Maliki Interdisciplinary Journal, 2025)
The Industrial Revolution 4.0 has rapidly accelerated civilizational changes, marked by digitalization and the rise of key technologies such as Artificial Intelligence (AI). This study examines the influence of AI on educational transformation, which is currently moving from conventional methods toward digital learning. AI serves as the core technology accelerating change through learning automation, personalization of materials, and providing data-based educational services. This transformation drives a pedagogical paradigm shift toward a model centered on students and technology. In this context, educators transition into facilitators, while learners are required to be more independent and possess adequate digital literacy. Although AI offers significant opportunities to improve learning effectiveness and access, it also presents challenges, including infrastructure readiness and the risk of moral and ethical degradation if humanitarian values are neglected. Therefore, the success of this transformation highly depends on institutional adaptation, the strengthening of technological curricula, educator training, and the establishment of strong AI ethics policies. This study is crucial for understanding the trajectory of educational development in the 4.0 era.